International organizations and small states : participation, legitimacy and vulnerability - Corbett, Jack (Political scientist); Xu, Yi-Chong; Weller, Patrick Moray (Bristol University Press, 2021)
This path-breaking book shows the efforts that small states have made to participate more fully in International Organizations (IOs). It highlights the challenges created by widened participation in IOs and develops a model of the dilemmas that both IOs and small states face as the norms of sovereign equality and the right to develop coincide.